Peperomia mangalbaria (Piperaceae), a new species from Sikkim Himalaya, India - Rai, Pramod; Mathieu, Guido (Phytotaxa, 2023)
Piperaceae is one of the most diverse plant families. Peperomia, the second largest genus of this family, has about 10 species in India which are distributed from the Northern Himalayas to the Southern Peninsula. Here we describe a new species of Peperomia from Sikkim Himalaya in northeastern India. A color plate, line drawing, distribution map, description, and taxonomic key to current species of Peperomia in Sikkim are provided.